Pornografia de vingança em redes sociais: perspectivas de jovens vitimadas e as práticas digitais - Mota, Bruna Germana Nunes (2015)
The internet gives us the access to information in real time and also allows the most varied content connections. With all these facilities, the Internet also provides dangers, called Virtual Crimes that are characterized by crimes committed through the virtual environment. They can be framed in the Brazilian Penal Code and violators are subject to penalties under the law. The test purpose is to discuss the Digital Educational Practices (DEPs) related to cybercrime, especially revenge porn. This has been a recurring problem among teenagers, so understanding how the DEPs can collaborate with the prevention of exposure teens on the web. The goal is to understand how the Digital Educational Practices may mediate the learning in the use of virtual networks, minimizing cyber crime and pornography for revenge. To conduct the research, was necessary to use concepts of DEPs, revenge porn and the Republic Constitution, since we treat the penalties for cybercrime. The research methodology is a study supported in literature searches as: Alfradique 2006, Burke 2008, Castells 2003, Grillo 2011 Junior 2006, Kenski 2007, Lemos and Maingueneau 2010, Pinheiro 2006 and Virilio 1996. It is based on oral plan, aimed to collect data in order to appropriate the historical facts. Through interviews, as one of the methodological procedures, all lines were recorded, as a way to approach the history of the subject, in other words, to seek a greater understanding of the vestiges of the past. In addition to interviews, we apply questionnaires with the students, teachers and a management representative. Those questionnaires proposed a more comparative and qualitative analysis. Trying to understand the occurrence of pornography related to young people, we clarify that the practice is well known among them, but the revenge of pornography term brings strangeness. So, between the results, it is concluded that between forty-four students, twenty one students met someone who was a victim of exposure and, at least, sixteen students have received pornographic materials, characterized with pornography for revenge. Currently, the expansion of the Internet and the facility of communication through instant messaging, such as WhatsApp application, have contributed to the increased dissemination of pornographic material. The fact is that something must be done to protect girls who are victims of exposure. The laws have been mild and hardly anyone is punished for committing the acts, because the photos are released through the application WhatsApp and are several people share and contribute to the dissemination of the material to a very large number of users, making it difficult in this way, the punishment of those involved in the release of the photos.